2017
DOI: 10.3390/cancers9090123
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Lymphoma Kinase in Cutaneous Malignancies

Abstract: Anaplastic lymphoma kinase (ALK) is a receptor tyrosine kinase that has been implicated in the pathogenesis of a variety of neoplasms. As suggested by its name, ALK was first described as part of a translocation product in cases of anaplastic large-cell lymphoma, with other genetic and cytogenetic ALK mutations subsequently coming to attention in the development of many other hematologic and solid organ malignancies. ALK has now been shown to play a role in the pathogenesis of several cutaneous malignancies, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 123 publications
(162 reference statements)
0
6
0
6
Order By: Relevance
“…In MCC, the function and key factors of the tumor microenvironment are quite poorly understood. Previous literature is yet indecisive on what are the actual ligands binding and activating the ALK receptor, but molecules such as Midkine (MDK) and heparin have been suggested [ 22 ]. Keeping in mind the correlation of MCPyV positivity and expression of ALK and p-ALK, ALK phosphorylation may be facilitated by the virus or by some other unknown factor present in the cells or by the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…In MCC, the function and key factors of the tumor microenvironment are quite poorly understood. Previous literature is yet indecisive on what are the actual ligands binding and activating the ALK receptor, but molecules such as Midkine (MDK) and heparin have been suggested [ 22 ]. Keeping in mind the correlation of MCPyV positivity and expression of ALK and p-ALK, ALK phosphorylation may be facilitated by the virus or by some other unknown factor present in the cells or by the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature does not offer much guidance regarding management of recurrences in MCC and individualized treatment on a case-by-case basis is often left to the clinician’s personal experience and judgement. Recent studies have examined the possible use of the anthracycline amrubicin as a systemic salvage therapy [ 14 ] and, due to the role of anaplastic lymphoma kinase (ALK) in MCC, the potential of the ALK inhibitor crizotinib may warrant further investigation [ 15 ]. A murine model study demonstrated that the histone deacetylase inhibitor vorinostat can stimulate the re-expression of human leukocyte antigen class-I on the surface of MCC cells, therefore potentially decreasing their ability to evade immune-surveillance [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Η ενδοκυττάρια πρωτεϊνική περιοχή του υποδοχέα έχει ενζυμική δράση, καταλύοντας τη μεταφορά μιας φωσφορικής ομάδας από την τριφωσφορική αδενοσίνη (ATP) σε ένα υπόλειμμα τυροσίνης της πρωτεΐνης του υποστρώματος(63). Αν και υπό αμφισβήτηση, δύο πρωτεΐνες έχουν ταυτοποιηθεί ως προσδέτες -αν και μη ειδικοί -του υποδοχέα ALK στα θηλαστικά: η μεσοκίνη (midkine) και η πλειοτροφίνη (pleiotrophin)(60,62,65). Αυτοί οι πολυπεπτιδικοί αυξητικοί παράγοντες έχουν την ιδιότητα να διμερίζονται και να προσδένονται με την ηπαρίνη σχηματίζοντας σύμπλοκα, ενώ εμπλέκονται σε μια πληθώρα κυτταρικών λειτουργιών όπως η νευρωνική ανάπτυξη, η μετανάστευση κυττάρων και η αγγειογένεση(60).…”
unclassified
“…Άλλοι πιθανοί προσδέτες του υποδοχέα ALK περιλαμβάνουν τον ειδικό οστεοβλαστικό παράγοντα 1 (osteoblast -specific factor 1 or OSF-1), το ρυθμιστικό πεπτίδιο με συγγένεια στην ηπαρίνη (Heparin Affinity Regulatory Peptide or HARP) και τον νευροτροφικό παράγοντα που προσδένεται στην ηπαρίνη (Heparin -Binding Neurotrophic Factor or HBNF), αν και το δυναμικό ενεργοποίησης του υποδοχέα των ανωτέρω πεπτιδίων παραμένει αμφιλεγόμενο(64). Τέλος, πρόσφατες μελέτες έδειξαν ότι οι μικρές πρωτεΐνες FAM150A και FAM150B που αποτελούν προσδέτες της λευκοκυτταρικής τυροσινικής κινάσης και εκφράζονται σε μεγάλο βαθμό στα επινεφρίδια, μπορούν και συνδέονται με την εξωκυττάρια περιοχή του ALK ενεργοποιώντας τον(63,65). Ο ρόλος του ALK στην ανθρώπινη φυσιολογία και ανάπτυξη δεν έχει γίνει ακόμη πλήρως κατανοητός και τα στοιχεία που έχουμε μέχρι σήμερα σχετικά με τη φυσιολογική του λειτουργία προέρχονται από μελέτες σε ζωικά μοντέλα.…”
unclassified
See 1 more Smart Citation